If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2+5)+(1+s)=12
We simplify the equation to the form, which is simple to understand
(2+5)+(1+s)=12
Simplifying terms in parentheses
(+7)+(1+s)=12
Remove unnecessary parentheses
+7+(1+s)=12
Remove unnecessary parentheses
+7+1+s=+12
We move all terms containing s to the left and all other terms to the right.
+1s=+12-7-1
We simplify left and right side of the equation.
+1s=+4
We divide both sides of the equation by 1 to get s.
s=4
| 3x-2=-11 | | a=pt+p | | X=-5x+4x | | 3x(4)-6=4x | | 0.5x+40=49 | | 6a-13=4a+9 | | -23=-2a-10-a | | 4y=3x+2 | | 5t+3(1-3t)= | | q+14=-6q | | 9x-1-7x-9= | | 5+a=10+1 | | -(5x-10)=5x | | 17x+17=289 | | 6x+9-9x+4= | | 3n+3.8=7.4 | | 5+a=10 | | 7x+11y=13 | | 5x-10-10x-4= | | 4(4y+2)=z(1+6y)+8 | | 5x+2x=63 | | -4(x+9)=-16 | | 3t-5=4(t+3) | | 7x-7=91 | | 4x-6=3x+9 | | -2(t+2)=12 | | x^2+2x-26=0 | | -14x=378 | | 3(y-3)=-9 | | 5-6(2+x)=x-4 | | -15.7=r-8 | | -5(6n-4)+4n= |